Pembuatan Pulp and Paper Berbahan Dasar Serat Kulit Pinang (Areca Catechu L.) dengan Penambahan Kitosan Sebagai Zat Aditif Antibakteri - Hasniar; Ida Hasmita; Eka Marya Mistar; Nadia Putri Mauliza; Kasturi (Jurnal Serambi Engineering, 2024)
The need for paper in Indonesia continues to increase along with population growth and progress in activities related to paper use. However, the supply of materials used to make wood pulp will also decrease over time. Continuous exploitation of forests will cause environmental problems. An alternative to reduce the impact on the environment is to replace the raw material for making non-wood paper which is rich in cellulose fiber. One non-wood raw material that is rich in fiber is areca nut shell. However, the current problem is that paper can be contaminated with microorganisms from free (dirty) air, dirty hands of people who handle it or from unsterile storage places. So,we need a new alternative to prevent this problem, namely by adding antibacterial additives to the paper. The method used is the process of delignification, filtration, drying, bleaching and adding chitosan additives. The conclusionsobtained that the optimum concentration of the NaOH cooking solution was found at a NaOH concentration of 10%, the optimum time was obtained at a delignification time of 6 hours, and the best concentration of chitosan additive was 6% with an inhibition zone of 7.01 mm. The inhibition zone obtained is in the weak category.